Community effects of electrification: evidence from Burkina Faso's grid extension - Moradi, A; Schmidt, M (University of Oxford, 2022)
Using true and pseudo panel data of localities and households, we study the effects of Burkina Faso’s large scale electricity grid expansion 2008-2017. We show that the timing of electrification was driven by engineering constraints and thus largely exogenous. We investigate the effects of electrification using a staggered difference-in-differences (DiD) approach, where not-yet treated communities serve as the control group. Despite low uptake of electricity at the household level, we find strong positive effects on luminosity at the community level. In terms of public goods provision, we find an increase in infant vaccination rates, electrified schools and drinking water provision. At the household level, we find increases in the ownership of electric appliances as well as an increase in bank patronage. Importantly, effects spill over to households that do not have an electricity connection.